Current problems and prospects of information technology implementation in higher education institutions of construction and transport - Mammadov, M.; Taghiyeva, T.; Talibzadeh, S.; Mammadov, T.; Мамедов, М.; Тагієва, Т.; Талібзаде, С.; Мамедов, Т. (Харківський національний автомобільно-дорожній університет, 2025)
The implementation of information technologies (IT) in higher education institutions of construction and transport has emerged as a critical factor in enhancing educational quality, institutional efficiency, and graduate competitiveness. Despite the significant potential of digital solutions, universities in these sectors face multiple challenges, including outdated IT infrastructure, limited financial resources, insufficient digital competencies among faculty and students, and resistance to organizational change. Specialized professional training in construction and transport further requires advanced modeling tools, simulation platforms, and sector-specific digital resources, which complicates the adoption of innovative IT solutions. Global experiences demonstrate the effectiveness of IT governance frameworks such as COBIT, ITIL, and CMMI in standardizing processes, increasing transparency, and ensuring continuous improvement. Emerging technologies–including big data analytics, learning analytics, virtual and augmented reality (VR/AR), building information modeling (BIM), digital twins, cloud services, and artificial intelligence (AI)-based tools–offer substantial opportunities to improve academic outcomes and operational efficiency. In the Azerbaijani context, progress has been observed in LMS adoption, blended learning, and administrative digitization; however, persistent barriers include uneven regional infrastructure, limited budgets, and scarce empirical evidence on IT governance in technical universities. Addressing these issues requires integrated strategies combining technological investment, faculty development, organizational reforms, and industry–university partnerships. Priority measures include establishing pilot projects for ITIL/COBIT implementation, developing specialized digital laboratories, embedding sector-specific digital competencies into curricula, and aligning national initiatives with global frameworks such as the UN Sustainable Development Goals and the EU Digital Education Action Plan. The study underscores the need for systematic evaluation of IT maturity and governance in construction and transport higher education, highlighting the importance of evidence-based approaches to digital transformation. Effective IT adoption in these specialized institutions necessitates a holistic approach that integrates infrastructure modernization, human capacity building, governance enhancement, and sectoral alignment to ensure sustainable development and prepare graduates for the demands of the digital economy.
Актуальні проблеми та перспективи впровадження інформаційних технологій у вищих навчальних закладах будівництва та транспорту
Keywords: information technology implementation; higher education; construction universities; transport universities; digital transformation; IT governance; digital competencies; educational technologies; Industry 4.0/5.0; learning analytics; впровадження інформаційних технологій; вища освіта; будівельні університети; транспортні університети; цифрова трансформація; ІТ-управління; цифрові компетентності; освітні технології; Індустрія 4.0/5.0; аналітика навчання; 378.014:004.738.5; 10.30977/ЕТК.2225-2304.2025.46.107